Inclusion and commitment as key pathways between leadership and nonprofit performance. Issue 1 (23rd May 2019) - Brimhall, Kim C.
Abstract: Given the projected growth of workforce diversity in the United States and the fact that heterogeneous workforces result in both positive (increased retention and performance) and negative (increased conflict and turnover) organizational outcomes, nonprofit leaders are faced with the challenge of effectively managing their workforces. Findings ways to ensure positive workplace outcomes, such as employee commitment (an emotional attachment to the organization) and performance, is especially critical for the overall functioning of nonprofit organizations. Using longitudinal multilevel path analyses, this study examined whether transformational leadership influenced work group performance through both creating a climate for inclusion and increasing employee affective commitment in a diverse nonprofit health care organization. Results indicate that transformational leaders help increase perceptions of inclusion, which improves employee commitment to the organization, and ultimately enhances perceived work group performance. This suggests inclusion and affective commitment as key factors for how leaders can increase nonprofit performance.